The Role of PKK: Driving MSMEs in Realizing a Creative Economy - Aryuni Shilvanawati; Putri Chahya Nigrum; Omar Syarifudin (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This study aims to analyze how Family Empowerment and Welfare (PKK) plays a role as a driver of Micro, Small and Medium Enterprises (MSMEs) in realizing a creative economy in Gubugsari Village. This study uses a qualitative approach by collecting data through interviews, observation, and documentation review. The results show that the PKK in Gubugsari Village plays an important role in empowering MSMEs through various programs, such as skills training, capital provision, and marketing assistance. These programs have encouraged the growth of creative industries in the village, such as handicrafts, culinary, and fashion. In addition, the PKK also plays a role in facilitating cooperation between MSMEs and other stakeholders to develop the creative economy ecosystem in Gubugsari Village. In conclusion, PKK has a significant role as a driver of MSMEs in realizing the creative economy in Gubugsari Village through various empowerment programs implemented.